Effect of Different Drying Techniques on Antioxidant Capacity of Two Romanian Red Grape Cultivars - Oprica LACRAMIOARA; Verdes ANDREEA; Poroch VLADIMIR; Creanga DORINA; Grigore MARIUS-NICUSOR (Tehran University of Medical Sciences, 2019)
No Abstract####